A comparison of two approaches to training visual analysis of AB graphs. Issue 2 (20th May 2015) - Wolfe, Katie; Slocum, Timothy A.
<x xml:space="preserve">Abstract</x> Visual analysis is the primary method of evaluating data in single‐subject research. Few studies have evaluated interventions to teach visual analys is skills. The purpose of this study was to evaluate systematic instruction, delivered using computer‐based intervention or a recorded lecture, on identifying changes in slope and level in AB graphs. Results indicated that both approaches were significantly more effective than a no‐treatment control condition but were not different from each other. We discuss the implications of these results for training and directions for future research.